The Use Of Whisper Game To Improve Students’ Vocabulary At The Fifth Grade Of SD Negeri 1 Tiakur - Alyona, Erlince; Lekawael, Rosina F. J.; Meyer, Fredi (Koli Journal : English Language Education, 2022)
Lack of vocabulary can influence the learning of English for all students at the elementary school level. Teaching vocabulary should be a priority for teachers to ensure students' understanding of English. The Whisper Game Technique is very effective in encouraging faster vocabulary learning, as students can memorize, accelerate, and enhance their knowledge capabilities. The aim of the research was twofold: 1) How can the Whisper Game be used to improve students' vocabulary in the fifth grade at SD Negeri 1 Tiakur MBD? 2) What are students' responses to the use of the Whisper Game to improve vocabulary in the Fifth Grade of SD Negeri 1 Tiakur MBD? The research employed Class Action Research (CAR), which consisted of two cycles, and data collection involved tests, questionnaires, and observations. The results of Cycle 1 showed that the average active student participation was 68%, and in Cycle 2, it increased to 100%. Therefore, there was progress of 32 points, indicating that the Whisper Game had a positive impact on improving students' vocabulary mastery